EXAMINATION OF SPERM DNA FRAGMENTATION FOR PATIENTS WITH HIGH CONTENT OF IMMATURE FORM OF SPERMATOZOA IN EJACULATE - Feskov, O.M.; Feskova, I.A.; Zhylkova, I.S.; Chumakova, N.O.; Somova, O.V. (World of Medicine and Biology, 2012)
The link between the content of the immature spermatozoa forms and spermatozoa with the fragmented DNA in ejaculate was examined for men with astheno-, oligo- and teratozoospermia. The correlation for the results of HBA-test and SCD-test was found out in 80.0 % of cases. The content of the spermatozoa with damaged DNA is significantly (р
Keywords: sperm DNA fragmentation; HBA-test; SCD-test